2018
DOI: 10.3122/jabfm.2018.03.170421
|View full text |Cite
|
Sign up to set email alerts
|

Living in “Cold Spot” Communities Is Associated with Poor Health and Health Quality

Abstract: Purpose:Little is known about incorporating community data into clinical care. This study sought to understand the clinical associations of cold spots (census tracts with worse income, education, and composite deprivation).Methods: Across 12 practices, we assessed the relationship between cold spots and clinical outcomes (obesity, uncontrolled diabetes, pneumonia vaccination, cancer screening-colon, cervical, and prostate-and aspirin chemoprophylaxis) for 152,962 patients. We geocoded and linked addresses to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“… 6 , 7 , 8 , 9 , 10 , 27 , 32 In this study, we assessed concordance between patient-reported social risks and community-level social deprivation among patients receiving care in a national network of CHCs. Building on previous work, 10 , 11 we defined cold spots as census tracts with SDI scores within the highest quartile nationally. Although there was some overlap between cold spot status and the presence of patient-level social risks, with 60.0% of those who reported at least 1 social need living in a cold spot census tract, 40.0% of patients who screened positive for at least 1 social risk did not live in a cold spot.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 6 , 7 , 8 , 9 , 10 , 27 , 32 In this study, we assessed concordance between patient-reported social risks and community-level social deprivation among patients receiving care in a national network of CHCs. Building on previous work, 10 , 11 we defined cold spots as census tracts with SDI scores within the highest quartile nationally. Although there was some overlap between cold spot status and the presence of patient-level social risks, with 60.0% of those who reported at least 1 social need living in a cold spot census tract, 40.0% of patients who screened positive for at least 1 social risk did not live in a cold spot.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Moreover, prior studies suggest that patients living in cold spots—defined as those census tracts with an SDI score in the highest quartile nationally (≥75)—have worse health outcomes relative to those in more resource-rich tracts. 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20] This critical challenge for primary care implementation scientists is addressed by several authors herein. Liaw et al 21 report on a novel approach to geocoded practice and population data to help primary care physicians identify and understand the effects of living in "cold spots"-areas with lower education, lower income, and greater composite scores of deprivation-on their patients. They used these methods to help 12 practices recognize that their patients living in cold spots had lower rates of receiving certain, but not all, preventive services and screening tests, a potential first step in targeting atrisk patients and developing mitigating interventions.…”
Section: Social Determinants Of Health and Health Promotionmentioning
confidence: 99%